Optimalisasi Produksi Usaha Pembuatan Tempe di Kabupaten Bangka Propinsi Kepulauan Bangka Belitung - Setiawan, Iwan; Sabto Pranata, Yudi (ENVIAGRO, 2008)
This research tried to know the generally condition of tempe production as small industry.Â  Besides finding out optimum level of tempe production and maximum profit could be obtained by tempe producers , this research also efforted to know the efficiency of small industries of tempe producer.Â  Field surveys were carried out in two sub regencies of Bangka, namely Kecamatan Sungailiat and Kecamatan Pemali.Â  Sub regencies were purposively chosen becaused in the locations were found many tempe producers were found and have been in place long time ago.Â  Primary and secondary data for this research included costs, quantities and price of tempe, and other relevant data.Â  The results indicated that industries of tempe production were still simply managed.Â  This condition may be reflected from the by appliances used in tempe production process.Â  There was no one tempe producers reached the optimum level of tempe production yet.Â Â Â  In this time tempe producers couldnât obtain maximum profit by only managing their production inputs.Â  The deficit in quantities of tempe was 34 % than the average optimum tempe production indicated that industries of tempe production didnât work efficiently yet.Â  The maximum profit of Rp 7.364.992,- could be obtained tempe producers while quantities by tempe achieved 16.083 batch.Â Â Â  Â Key words :Â  Optimalization, Tempe, Production, Bangka, Maximum Profit.